2018
DOI: 10.1159/000488269
|View full text |Cite|
|
Sign up to set email alerts
|

Dysregulated MiR-3150a-3p Promotes Lumbar Intervertebral Disc Degeneration by Targeting Aggrecan

Abstract: Background/Aims: Low back pain has become one of the most common musculoskeletal diseases in the world. Studies have shown that intervertebral disc degeneration (IDD) is an important factor leading to low back pain, but the mechanisms underlying IDD remain largely unknown. Research over the past decade has suggested critical roles for microRNAs (miRNAs) in natural growth and disease progression. However, it remains poorly understood whether circular RNAs participate in IDD. Methods: Clinical IDD samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…These data suggest that melatonin reduces TNF‐α and IL‐1β production not only through the PI3K/AKT, ERK, and NF‐κB pathways, but also via upregulation of miR‐3150a‐3p expression. The inhibition of miR‐3150a‐3p expression has been indicated in breast cancer and, in a recent study, upregulation of miR‐3150a‐3p was found to promote lumbar intervertebral disk degeneration by targeting aggrecan …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These data suggest that melatonin reduces TNF‐α and IL‐1β production not only through the PI3K/AKT, ERK, and NF‐κB pathways, but also via upregulation of miR‐3150a‐3p expression. The inhibition of miR‐3150a‐3p expression has been indicated in breast cancer and, in a recent study, upregulation of miR‐3150a‐3p was found to promote lumbar intervertebral disk degeneration by targeting aggrecan …”
Section: Discussionmentioning
confidence: 98%
“…The inhibition of miR-3150a-3p expression has been indicated in breast cancer and, in a recent study, upregulation of miR-3150a-3p was found to promote lumbar intervertebral disk degeneration by targeting aggrecan. 54 Melatonin receptors consist of 7 transmembrane-spanning proteins and two major subtypes, MT1 and MT2, encoded by the MTNR1A and MTNR1B genes, respectively. 55 The localization of these two receptors differs physically, indicating that they play different roles and functions in various situations.…”
Section: Discussionmentioning
confidence: 99%
“…We identified coexpression modules based on expression of all lincRNAs and PCGs using WGCNA R software . WGCNA module detection was conducted using an unsigned type of topological overlap matrix (TOM), a power β of 10, a minimal module size of 20, and a branch merge cut height of 0.25 . A FDR value of <0.05 by the permutation test was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…[29][30][31][32] WGCNA module detection was conducted using an unsigned type of topological overlap matrix (TOM), a power β of 10, a minimal module size of 20, and a branch merge cut height of 0.25. 33 A FDR value of <0.05 by the permutation test was considered significant. The dysfunctional lincRNA modules were enriched with differentially expressed lincRNAs (at least 1 lincRNA/module) or PCGs (hypergeometric test, FDR < 0.05).…”
Section: Functional Enrichment Analysis Lincrna-pcg Co-expression Modmentioning
confidence: 99%
“…Our results found miR-4450 was significantly up-regulated in IDD, which highlights its possible role in the pathogenesis of IDD, and the inhibition of miR-4450 may help protect NP. Two other studies further confirmed this trend [25,26]. Therefore, the overexpression of miR-4450 in NP of IDD patients highlights its possible role in the pathogenesis of IDD, and the inhibition of miR-4450 may help protect NP.…”
Section: Discussionmentioning
confidence: 64%